Factors Related To Toddler Visits At The Kenanga Posyandu In Jurang Mangu Timur Village For The Period Of May 2023 – April 2024 - Sekar Hara Ayu Ningrum; Rahma, Nurika; Anah Sugihanawati; Ernawati (Universitas STRADA Indonesia, 2025)
Posyandu has an important role in making it easier for the community to check their health, one of the goals of which is to monitor nutrition in toddlers to prevent stunting. Riskesdas data showed that the percentage of routine weighing of toddlers in Banten is still very low. The purpose of the study was to find out predisposition factors (age of toddlers, maternal age, parity, knowledge, education, occupation, attitude, income), supporting factors (distance from the posyandu), driving factors (family support, cadre roles) related to visits by toddlers at the Kenanga Posyandu, East Jurang Mangu Village, for the period of May 2023 – April 2024.